Cleo's Secret herbal soap with aromatherapy - Gueta, Angelo; Lodo, Marjorie Jane; Munar, Toni Mariz; Reyes, Princess Emma
Cleo's Secret is a saluyot-based herbal soap with aromatherapy that can whiten, moisturize and prevent skin aging. This caters to the people who want to use natural resources as their beauty agent. In addition, it also serves the purpose of giving a relaxing feeling. From the Market Study, it has been proven that there is a gap between the current supply and demand in the market. From this demand, a target market share was narrowed down to focus on the herbal soap industry. Marketing advertisements and promotions were planned according to the target market share. Costs were calculated and were carried out to the technical analysis. With the technical analysis, the process, raw materials, equipment, suppliers were evaluated to come up with the best and optimum level raw materials to Cleo's Secret. Capacity planning was done to allot products to the changing demand and facility planning was carried out to find out the optimum location of the plant. Financial analysis is a critical part wherein the profitablility of Cleo's Secret was determined. After all the financial statements have been calculated and financial analysis was done to evaluate the desirability of the producing Cleo's Secret,it was concluded that the financial revenues exceeded the cost and Cleo's Secret is desirable. For the socio-profitability analysis, not only the financial benefits were considered. Economic benefits to different elements such a consumers, country, economy and local suppliers were analyzed. Cleo's Secret cannot be executed with profitability as the main goal. It also serves to fulfill the needs of the customers and the country. Considering the status of saluyot in the country, using saluyot as a main ingredient to herbal soap pioneers the utilization of underused resources of the Philippines. Based on the conducted market analysis, Technical analysis, financial analysis and socio-profitability analysis, Cleo's Secret is indeed desirable and commercially viable.